Introduction to nanotechnology in eco-efficient construction - Pacheco-Torgal, F. (2018)
This chapter briefly reviews recent developments on the field of nanotechnology. Patent production by top countries are reviewed.  Some nanotech limitations are highlighted. The case of nanotechnology influence on the development of eco-efficient construction and building materials and its contribution for 2030 agenda for sustainable development is briefly addressed. A book outline is included.